O uso de látex natural como barreira oclusiva na regeneração óssea guiada em defeitos críticos na calvária de coelhos - Ereno, Cibele (2007)
The latex extracted from Hevea brasiliensis is a biocompatible material. The film produced after its polymerization has several important characteristics: high mechanical resistance, elasticity, flexibility, low cost and capability for angiogenesis induction. This work consists of a study of the use of a natural latex film as an occlusive membrane for guided bone regeneration technique. Twenty four rabbits were placed in two groups - experimental and control group. Critical size defects (2cm X 1cm) were made surgically in rabbits calvarial. Two latex membranes were implanted in each animal of the experimental group one on the duramater and the other on the surface of the defect. In the control group the defect was filled by blood clot. After 15, 30, 60 and 120 days, the animals were euthanized. The regenerated bone samples were removed and macroscopic, microscopic, radiographic and electron spin resonance analyses were performed. The experimental group results related to the bone healing were better than the ones in the control group in all analyses made. It can be concluded that the natural latex biomembrane acted as an efficient occlusive barrier in the bone guided regeneration technique.